Diagnostic Delay of Pulmonary Embolism in COVID-19 Patients - Melazzini, Federica; Reduzzi, Margherita; Quaglini, Silvana; Fumoso, Federica; Lenti, Marco Vincenzo; Di Sabatino, Antonio (Frontiers in Medicine, 2021)
Pulmonary embolism (PE) is a frequent, life-threatening COVID-19 complication, whose diagnosis can be challenging because of its non-specific symptoms. There are no studies assessing the impact of diagnostic delay on COVID-19 related PE. The aim of our exploratory study is to assess the diagnostic delay of PE in COVID-19 patients, and to identify potential associations between patient- or physician-related variables and the delay. This is a single-center observational retrospective study that included 29 consecutive COVID-19 patients admitted to the San Matteo Hospital Foundation between February and May 2020, with a diagnosis of PE, and a control population of 23 non-COVID-19 patients admitted at our hospital during the same time lapse in 2019. We calculated the patient-related delay (i.e. the time between the onset of the symptoms and the first medical examination), and the physician-related delay (i.e. the time between the first medical examination and the diagnosis of PE). The overall diagnostic delay significantly correlated with the physician-related delay (p<0.0001), with the tendency to a worse outcome in long physician-related diagnostic delay (p=0.04). The delay was related to the presence of fever, respiratory symptoms and high levels of lactate dehydrogenase. It is important to rule out PE as soon as possible, in order to start the right therapy, to improve patient’s outcome and to shorten the hospitalization.